Developing adaptive responses to contextual changes for sustainable agricultural management: The role of social capital in the Arborea district (Sardinia, Italy). (January 2017) - Ruiu, Maria Laura; Seddaiu, Giovanna; Roggero, Pier Paolo
Abstract: This article investigates the role played by social capital (in terms of bonding, bridging and linking social capital) in developing adaptive responses to contextual changes (environmental, social and economic) at the local scale. Three questions guided the research: can social capital produce resilience and collective action? Could environmental barriers be turned into opportunities? Can social capital contribute to long-term adaptation to change? Results obtained from a qualitative research conducted in the Arborea district (Sardinia, Italy) show how collective actions to adapt to contextual changes are both results and generators of robust social capital. On the one hand, social capital contributes towards increasing resilience by generating collective responses to contextual changes without compromising the structural functions of the system; on the other hand, the lack of a clear regulatory framework for facilitating the development of local collective adaptive responses, depresses foresight strategies. Highlights: The lack of a clear regulatory framework depresses foresight adaptation strategies. Formalised organisations enhance people's confidence to take part in collective actions. Dialogical spaces might increase bonding, bridging and linking social capitals. Bonding, bridging and linking social capitals increase resilience at the community level.